Sufisme Idries Shah Sebagai Kontra Formlisme Agama - Husnul Qodim (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2022)
This paper describes Idries Shah's Sufism thinking as a counter to religious formalism. Because religious formalism will give birth to an exclusive nature and lead to religious-based radicalism. Therefore, this study really needs to be done in order to realize religious people who are inclusive and tolerant. This research was carried out by library research, by analyzing the original writings of Idries Shah. Data were collected through documentation techniques. The results of this research show that there are four religious attitudes that can liberate religious people from religious formalism from Idries Shah's perspective, including the following: first, humanity or humanity, these attitudes will lead a person to flexibility, conditioned or controlled in his beliefs. Second, discipleship. This stage trains one's capacity towards self-realization, which then aims at self-purification. Third, real capacity. It is a condition in which real capacity develops. At this stage the individual's awareness will rise to the level of perception of the real reality. Fourth, attunement with the divine or conformity with the divine will